1944
DOI: 10.1084/jem.80.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Properties of Preparations of Pr8 Influenza Virus

Abstract: The biophysical properties of several preparations of PR8 influenza virus have been studied. Electron micrographs showed slightly irregular, circular particles with an average diameter of 115 mµ and a standard deviation of the distribution of diameters of 15 per cent. The specific volume was determined with a pycnometer to be 0.79. The sedimentation rate was found to vary inversely with the concentration of virus. The extrapolated value for one preparation was 722 Svedberg units and the value for another prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1945
1945
1983
1983

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Since it has been shown that this slight activity is undoubtedly due to contamination with a trace of virus (27), it is apparent that independent particles of normal protein exist in centrifugally isolated preparations of F12 and of Lee influenza viruses. Sedimentation and electrophoretic studies (11,12) together with the serological tests on centrifuge fractions described in the present report, indicate that the same situation prevails with comparable PR8 virus preparations. However, when preparations of virus are obtained by adsorption on and elution from red cells followed by an appropriate number of cycles of differential centrifugation, or when they are got by electrophoretic fractionation, or by centrifugal fractionation, it can be shown that these preparations are essentially devoid of independent particles of the sedimentable component characteristic of normal allantoic fluid.…”
Section: Relation Of Normal Antigen To the Particles Bearing Virus Activitysupporting
confidence: 73%
See 1 more Smart Citation
“…Since it has been shown that this slight activity is undoubtedly due to contamination with a trace of virus (27), it is apparent that independent particles of normal protein exist in centrifugally isolated preparations of F12 and of Lee influenza viruses. Sedimentation and electrophoretic studies (11,12) together with the serological tests on centrifuge fractions described in the present report, indicate that the same situation prevails with comparable PR8 virus preparations. However, when preparations of virus are obtained by adsorption on and elution from red cells followed by an appropriate number of cycles of differential centrifugation, or when they are got by electrophoretic fractionation, or by centrifugal fractionation, it can be shown that these preparations are essentially devoid of independent particles of the sedimentable component characteristic of normal allantoic fluid.…”
Section: Relation Of Normal Antigen To the Particles Bearing Virus Activitysupporting
confidence: 73%
“…From infectious allantoic fluid of chick embryos, highly purified preparations of PR8 influenza virus have recently been obtained which are homogeneous in the analytical ultracentrifuge and in the Tiselius electrophoresis apparatus and which consist of particles about 100 m/~ in diameter (9)(10)(11)(12)(13). When these particles are sedimented it can be shown that the units carrying infectivity and chick cell agglutinating activity sediment at the same rate (14).…”
mentioning
confidence: 99%
“…It is apparent from the electron micrographs as well as from the sedimentation data given above that the size and shape of the particles in highly purified preparations of mouse lung PR8 virus do not differ significantly from those of preparations from allantoic fluid (10,12).…”
Section: Properties Of Purified Mouse-lung Virus Biological Propertiementioning
confidence: 86%
“…Based on sedimentation properties and electron microscopic measurements, influenza A viruses were estimated to have a particle weight in the range of 270-290 x 10 6 daltons (Lauffer and Stanley, 1944;Sharp et at., 1945;Schramm, 1954). However, a much lower value of 151 x 10 6 was obtained for fowl plague virus based on sedimentation and diffusion coefficients (Schafer et at., 1952;Schramm, 1954).…”
Section: Compositionmentioning
confidence: 99%